Myocardial structural protein expression in umbilical cord blood mesenchymal stem cells after myogenic induction. (17th July 2013) - Ma, Nan; Ding, Fangbao; Zhang, Junwen; Bao, Chunrong; Zhong, Hong; Mei, Ju
Abstract: To assess the effects of three methods of inducing myogenic cells differentiation, umbilical blood mesenchymal stem cells (UCMSCs) from nearly full‐term pregnancy mongrel dogs were purified and cultured. Fourth‐passage UCMSCs were used to detect surface antigens, including CD11a, CD11b, CD29, CD34 and CD71. The cells were induced by 5‐azacytidine (5‐aza), myocardial lysates and myocardial induced fluid. Positive expression of Nkx2.5, α‐actin, desmin, β‐MHC and troponin‐I (TN I) were detected after 3 weeks. The immunohistochemical results were CD11a (−), CD11b (−), CD34 (−), CD29 (+) and CD71 (+). Nkx2.5 was detected in 5‐aza group, myocardial lysates group and myocardial induced fluid group. Semi‐quantitative analysis showed Nkx2.5 expression significantly higher in myocardial lysates group than in the 5‐aza group or myocardial‐induced fluid group ( P < 0.05), but there was no significant difference between the 5‐aza and myocardial‐induced fluid groups for Nkx2.5 expression ( P > 0.05). MSCs did not express myocardial structural proteins before differentiation, but α‐actin, desmin, β‐MHC and troponin‐I were present after differentiation. The positive expression of four proteins differed with the differentiation conditions. The UCMSCs can be differentiated into myogenic cells by three methods, but the degrees of differentiation are inconsistent. Our results show that the effects of 5‐aza and myocardial lysates are better than that of myocardial induced fluid.